Compost and Biochar to Promote Soil Biological Activities under Sweet Potatoes Cultivation in a Subtropical Semiarid Region. (30th November 2020) - Navarro, Josabeth; Salazar, Jahdiel; Kang, James Jihoon; Parsons, Jason; Cheng, Chu-Lin; Castillo, Alexandria; Pujol Pereira, Engil Isadora
Abstract : South Texas is located in a subtropical semiarid climate, and due to high temperature and irregular precipitation, farmers opt to leave their fields fallow during the summer months jeopardizing overall soil health. We evaluated whether sweet potato ( Ipomoea batatas ) cultivation coupled with drip irrigation could restore soil biological activities compared with bare fallow. Additionally, because sweet potatoes have high demand of soil nutrients, especially potassium (K), we evaluated the nutrient supply of locally sourced soil amendments. Sweet potato was cultivated during summer 2018 in McAllen, Texas, under control (no fertilizer), NPK (synthetic fertilizer), RC (yard-waste compost), and AC (compost produced under an enhanced composting process), and biochar (gasified walnut shell at 900°C), each with three replicates. Soil amendments were applied at different amounts to result in a rate of 80 kg K ha −1 . Soil biological indicators were microbial biomass phosphorous, phosphatase activity, and the rate of fluorescein diacetate hydrolysis (FDA). Available nitrogen, phosphorus, potassium, and sodium were also quantified. Aboveground biomass and storage root yield estimated sweet potato's agronomic performance. Cultivation and irrigation stimulated soil enzyme activities and microbial biomass-phosphorous. Sweet potato yields were the highest in NPK treatment but still 2.8 times lower than variety's potential yield. Storage root yield was inversely related to aboveground biomass, suggesting that growing conditions benefited the production of shoot versus roots. Both biochar and AC treatments stimulated FDA rates and K availability. Soil pH and sodium concentration increased in all treatments over the growing season, possibly due to river-sourced irrigation water. Together, these findings show that crop cultivation promoted soil biological activities and the maintenance of nutrient cycling, compared to bare-fallow conditions. For a better agronomic performance of sweet potato, it would be necessary to identify management practices that minimize increase in soil pH and salinity.